Translating Translingual Writings into Authors’ Native and Non-Native Languages: a Study of Novels by Gary Shteyngart and Aleksandar Hemon and Their Russian Translations - Ekaterina S. Lebedeva (Polylinguality and Transcultural Practices)
Translingual fiction i.e. works by those writers who have chosen to write in a language other than their native one has been extremely popular in the academic community. Domestic and foreign linguists and literary scholars have already identified certain features of translingual literature (for example, a particular worldview of a translingual author, certain stylistic devices that help to convey translingualism). However, not only academic community, but also the book market respond to the phenomenon of translingual writers with a need to translate this literature into different languages. Unfortunately, modern translation theory and practice lack full and comprehensive description of the translation strategies to be applied when translating literary translingualism. The objective of the present study is to identify the strategies used by translatorsto preserve and convey the writer’s transcultural identity, as well as to answer the question: howto preserve otherness that an English-language reader of translingual literature experiences, and which can be lost when it is translated into the writer's native language. This paper aims to study the strategies used by translators of novels by Russian-American and American-Bosnian authors. “Super Sad True Love Story” by Gary Shteyngart and “The Lazarus Project” by Aleksandar Hemon were selected as research material. As a result of the research based on the comparative method, linguacultural, contextual and syntactic analysis, it was possible to form a list of techniques for conveying the author’s translingualism when translating into the author’s native and non-native languages and also to draw a conclusion about the cases in which the main feature of translingual works (the feeling of otherness) is preserved and lost when translating foreign inclusions and other examples of translingual creativity into Russian.